Tinjauan Yuridis Terhadap Pemusnahan Barang Bukti Tindak Penyalahgunaan Narkotika di Kejaksaan Negeri Makassar - Syamsuddin, Rahman; Taufik, Ahmad (Alauddin Law Development Journal, 2021)
Abstract This research tries to raise the issue of how the legal provisions govern the implementation of the process of destroying narcotic evidence in carrying out investigations of criminal cases in the Makassar District Attorney’s Office? And also what factors hinder the destruction of evidence of narcotics misuse in Makassar District Prosecutors Office? From the results of research in the field then the author tries to examine each obstacle encountered in the process of eradicating narcotics evidence and find out what efforts can be taken so that the existing problems can be minimized or any form of non-conformity can be effectively addressed. This research was conducted in the jurisdiction of the Makassar District Attorney. The research method in this thesis is Empirical Law research or Field Research in which this research is conducted by basing primary data and secondary data. Where the primary data, namely data obtained from interviews in the form of direct question and answer, with the aim to get the data. This method is useful as a measurement tool. While secondary data were obtained from literature studies, references, laws and regulations and legal documents obtained from the study site. The data is then analyzed qualitatively to obtain answers to the problems in this thesis by carrying out three stages, namely data reduction, data presentation and drawing conclusions. From the results of this study, the authors found facts that occurred in the field that were not in accordance with the guidelines on the destruction of narcotics evidence contained in the legislation due to several internal conditions such as inadequate storage facilities and also the time given in destruction of evidence that is too short and the budget for implementing the destruction of evidence is very limited, causing inconsistencies in the implementation of destruction of narcotics evidence to meet the standards that have been applied. Keywords: Narcotics, Evidence, Destruction